Evaluation of Unscheduled Return Visits to the Pediatric Emergency Department and Risk Factors for Admission After Return Visit. Issue 2 (27th February 2022) - Kurt, Funda; Hanalioğlu, Damla; Can, Fatmanur; Kurtipek, Fatma Eren; Yakut, Halil İbrahim; Misirlioğlu, Emine Dibek
Abstract : Objective: Unscheduled return visits to the emergency department (unscheduled RTED) increase both the workload and overcrowding in the emergency department. The aim in the present study is to identify the patient groups that require more careful and closer follow-up to reduce the rates of unscheduled RTED and hospital admissions after a return visit. Methods: Among the patients admitted to the emergency department of our hospital between 2016 and 2017, those who made an unscheduled RTED within 72 hours after their first visit to the emergency department were evaluated retrospectively. Results: Of the 137, 787 eligible children, 3294 (2.8%) made unscheduled RTEDs within 72 hours. The median age was 28 months, and 1848 (57.6%) were male patients. The admission rate at the return visit was significantly higher among children younger than 2 years, in the patients presenting with respiratory complaints and severe acute conditions, and in those who presented to the emergency department for the first time during the department's busiest hours. The risk of admission upon a return visit to the emergency department was 2.7 times higher in the male sex, 5.4 times higher in children younger than 2 years, 5.9 times higher in patients with respiratory complaints, 4.9 times higher in patients with gastrointestinal tract complaints, and 27, 000 times higher in patients with severe acute conditions. Conclusions: Unscheduled RTED and hospitalization rates can be reduced with more careful evaluation of young children, patients with respiratory and gastrointestinal complaints and those who apply during emergency department busiest hours.